E-book Usage among Chemists, Biochemists and Biologists: Findings of a Survey and Interviews. - Yuening Zhang; Roger Beckman (Issues in Science and Technology Librarianship)
An e-book usage survey was sent through departmental mailing lists to the graduate students, scientists and faculty members of the Chemistry Department and Biology Department of Indiana University, Bloomington (IUB). Several faculty members, scientists and graduates students from the Chemistry Department and Biology Department were also contacted for interviews about their e-books usage experience. The purpose of the survey and interviews was to get a better understanding of users' e-book awareness, what advantages they find in using e-books, what concerns they have about e-book purchases and features, and what the library could do to better promote the use of e-book resources on campus. Reprinted by permission of the publisher.